Gpr171 regulates embryonic hematopoietic stem cell emergence via ERK1/2 and Notch signaling - Kun Zhou; Hongyan Liu; Kai Zhu; Longhai Yu; Peng-Fei Xu; Yan Li (Proceedings of the National Academy of Sciences, 2026)
Hematopoietic stem cells (HSCs), which sustain lifelong blood cell production, emerge from hemogenic endothelium during embryonic development through the regulation of multiple signaling pathways. However, generating functional HSCs in vitro remains challenging, underscoring gaps in understanding the underlying mechanisms. Here, we identify GPR171, a P2Y-family G-protein-coupled receptor (GPCR), as a critical regulator of vertebrate embryonic HSC specification. Gpr171 is highly expressed in hemogenic endothelium and hematopoietic stem and progenitor cells. A deficiency in Gpr171 results in severe embryonic HSC deficits but does not impair vasculogenesis and primitive hematopoiesis. We further find that its endogenous ligand, coded by pcsk1nl , cooperates with Gpr171 to enhance HSC generation. Mechanistically, Gpr171 activates ERK1/2 and Notch signaling pathways independently and synergistically to promote HSC generation. Pharmacological treatment of zebrafish embryos with the human GPR171 ligand BigLEN significantly increases HSC numbers. Moreover, GPR171 signaling is evolutionarily conserved, as GPR171-deficient murine embryos also exhibit a significant reduction in functional HSCs. Overall, our findings reveal GPR171 as an evolutionarily conserved regulator of embryonic HSC specification and suggest its potential for translational applications in stem cell–based therapeutics.